Determinants and Outcome of Safe Second Trimester Medical Abortion at Jimma University Medical Center, Southwest Ethiopia - Yibeltal Siraneh; Ahadu Workneh (Hindawi Limited, 2019)
Background. Although the vast majority of abortions are performed in the first trimester, still 10-15% of terminations of pregnancies have taken place in the second trimester globally. As compared to first trimester, second trimester abortions disproportionately contribute to maternal morbidity and mortality especially in low-income countries where access to safe second trimester abortion is limited. The objective of this study was to identify factors affecting and outcome of induced safe second trimester medical abortion in Jimma University medical center, Southwest Ethiopia. Methods. Institution based cross-sectional study design was used to conduct a study among women who seek safe second trimester medical abortion services and admitted at gynecology ward. All (201) eligible study subjects included were those who came for safe medical abortion service during data collection period. Data collected using pretested structured questionnaire through exit-interviewing and some clinical data abstracted from their chart. The data was entered into EpData version 3.1 then exported to SPSS version 21.0 for analysis. Variables with P-value less than 0.25 in bivariate analysis were entered into the final predictive model. Multivariable logistic regression was used to identify determinants with 95% CI and P-value < 0.05. Hosmer and Lemeshow test were used to check model fitness at P-value of 0.05. Ethical clearance was obtained and confidentiality kept using codes and patient's chart number. Results. In this study the response rate was 98.1%. Out of 201 women who participated in the study and were addmitted for safe second trimester medical abortion, 154 (76.6%) of them had complete abortion without any complication while the remaining 47 (23.4%) had incomplete abortion with one or more complication. Previous experience of abortion [AOR= 6.00, 95% CI= (3.77, 8.88)], gestational age [AOR=0.90, 95% CI= (0.07, 0.99)], parity [AOR=2.38, 95% CI= (1.04, 3.69)], cervical status [AOR=8.00, 95% CI= (5.72, 10.02)], overall waiting time for more than two weeks [AOR=0.53, 95% CI= (0.50, 0.96)], overall waiting time for two weeks [AOR=0.05, 95% CI= (0.01, 0.45)], and moderate anemia -(Hgb:7-10g/dl)-[AOR=0.07,95% CI= (0.01, 0.16)] were independent predictors for outcome of safe second trimester medical abortion. Conclusion. This finding implied that proportion of complete abortion without any complication overweighs incomplete abortions with one or more complication through induced safe second trimester medical abortion method. The outcome is strongly determined by gestational age, cervical status, previous experience of abortion, parity, moderate anemia, and overall waiting time. Induced second trimester medical abortion is already known as an effective and safe method. However, much should be done to reduce proportion of incomplete abortions by minimizing overall waiting time through intervening at low gestational age. Therefore, it is recommended that safe second trimester medical abortion services should be continued under a certain legal circumstances so as to reduce maternal morbidity and mortality.